A carnavalização em charges com temática racista: uma análise dialógica. - Guedes, Niege da Rocha (2022)
This thesis investigates the use of carnival language in racist-themed cartoons, published between 2019 and 2021 in Brazil, in order to analyze the axiological assumptions of the author’s voices in the cartoons. For a better understanding of the reality of black people in Brazil, it will be necessary to make considerations about how racism is structured and rooted in Brazilian society, and about black people's struggle in the country, which persists to this day, as well as to understand the reality refracted by the authors of the cartoons. The analysis will be based on the dialogic perspective of discourse, by Bakhtin (2003, 2010, 2015, 2016 and 2018) Voloshinov (2013 and 2017) and Medvedev (2019), among other authors who study this theory, taking into account issues related to the understanding of the ideas present in the cartoons, which will indicate the axiological position that the cartoonists assume, since, for these authors, language is made up of values, and these values express the social posture of the groups. Therefore, it is important to investigate which discourses are constitutive of racism to analyze how the carnival language present in racist-themed cartoons builds the axiological assumption of cartoonists against prejudice and racial violence. In addition, through carnival language, cartoonists criticize racism, dialogue with racist and anti-racist discourses circulating in society, and express values of the discursive moment in which they create the cartoons. In this way, the cartoons present society inside out, show injustices, and reveal perverse actions against black people. With this, through the verbal and visual text, constitutive of the cartoons, the cartoonists encourage the reader to reflect on their reality and to react to an event, which may cause changes in this reality. For this study, six cartons will be analyzed. They will be organized into three groups. Each group will contain two cartoons that dialogue with each other about the same event, and with other circulating discourses, a constitutive principle of dialogic theory. It will be examined how carnivalization shows and, at the same time, expresses the axiological assumption of combating racism in Brazil, with irony and sarcasm. The analysis will be qualitative because we aim at extending issues related to carnivalization in cartoons, and its importance for the apprehension of the axiological assumption of the cartoonist and the understanding of the senses. In addition, we will be able to observe how the cartoon can contribute to the awareness of the changing process of a certain group. We concluded that the selected cartoons denounce how black people are treated and show how the socioeconomic prestige of the white elite ends up reinforcing prejudice in Brazil. Thus, image and linguistic elements are mixed for the construction and understanding of the text and for the characterization of the genre. Therefore, they contribute to the understanding of the author's axiological assumption, which is always impregnated with values from a context that will determine the intonation of the speech and the appropriate image to express the anti-racist position assumed by the cartoonists in the analyzed cartoons.